(untitled) (Berlin,New York, 2006)
Staab and Stuckenschmidt structured the selected contributions into four parts: Part I, "Data Storage and Access", prepares the semantic foundation, i.e. data modelling and querying in a flexible and yet scalable manner. These foundations allow for dealing with the organization of information at the individual peers. Part II, "Querying the Network", considers the routing of queries, as well as continuous queries and personalized queries under the conditions of the permanently changing topological structure of a peer-to-peer network. Part III, "Semantic Integration", deals with the mapping of heterogeneous data representations. Finally Part IV, "Methodology and Systems", reports experiences from case studies and sample applications
Keywords: Semantic Web,Peer-to-peer architecture (Computer networks),Web ngữ cảnh